Case report: Experience with the Cube Navigation System in complex access routes during CT-guided lumbosacral infiltration therapy - Diepers, Michael; Gruber, Philipp; Remonda, Luca; Berberat, Jatta (Frontiers in Surgery, 2023)
Purpose: CT-guided infiltrations are a mainstay in the treatment of lower back pain. Needle placement is usually performed using the free-hand method, where the translation from the planned needle angle to the actual needle insertion angle is estimated. However, the free-hand method is especially challenging in cases where a double oblique access route (out-of-plane) rather than an in-plane route is necessary. In this case series, we report our experience with the patient mounted Cube Navigation System to guide needle placement for complex access routes in lumbar pain therapy. Research design and methods: We retrospectively analyzed the cases of five patients in whom a double oblique access route was necessary for CT-guided lumbar infiltration pain treatment. Each of those procedures was done using the Cube Navigation System to provide navigational guidance. The mean patient age was 69±13 years (range 58-82 years; all females). Technical success, procedure time and number of control scans were determined retrospectively. Results: Technical success (i.e. positioning and accuracy) was obtained in all cases. Mean procedure time was 15±7min (10-22min), on average 2±1CT control scans were performed. There were no complications or material failures reported in the present study. Conclusion: Double oblique punctures with the Cube Navigation System in this initial case series of complex access routes at the lumbar spine were accurate and the procedure was time efficient. In the authors’ view, the Cube Navigation System has the potential to improve needle guidance for complex access routes, especially considering the ease of use of the device.